2015
DOI: 10.1177/0194599815587700
|View full text |Cite
|
Sign up to set email alerts
|

Laryngoscope Illuminance in a Tertiary Care Medical Center

Abstract: Twenty-eight percent of laryngoscopes in a tertiary care hospital exhibit substandard illuminance; these results corroborate the findings of our inaugural study on this subject. Consequently, our hospital is instituting changes to reduce the likelihood of substandard performance by laryngoscopes in circulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 12 publications
2
3
0
1
Order By: Relevance
“…The findings of this study were in keeping with previous studies, 5,7,14 as well as the clinical impression of poor laryngoscope illuminance. Only 8 (18.6%) laryngoscopes of the 43 tested met the ISO Standard after 10 minutes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The findings of this study were in keeping with previous studies, 5,7,14 as well as the clinical impression of poor laryngoscope illuminance. Only 8 (18.6%) laryngoscopes of the 43 tested met the ISO Standard after 10 minutes.…”
Section: Discussionsupporting
confidence: 91%
“…Studies previously conducted have shown that the light produced may be of varying intensity and that the laryngoscopes functionality may not always be reliable. [3][4][5][6][7][8] The two most common lighting mechanisms of laryngoscopes are the "bulb-on-blade" or incandescent type, and the "bulbin-handle" or fibreoptic type. The light source or bulb of an incandescent laryngoscope is mounted on the blade of the laryngoscope.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sabe-se que mais da metade dos eventos adversos com equipamentos cirúrgicos podem ser evitados com a manutenção em dia e a verificação de tais aparelhos antes de cada cirurgia pela própria equipe multiprofissional [6][7][8][9][10][11] . Apesar da ocorrência de eventos adversos durante intervenções cirúrgicas ser reconhecida como um problema de saúde pública, tal problema ainda não é reconhecido pelas instituições de saúde [6][7][8][9][10][11] . Isso se deve a deficiências na gestão organizacional, econômica e financeira das instituições, sobretudo nos países em desenvolvimento.…”
Section: Discussionunclassified